Hunting magic eels recovering an enchanted faith in a skeptical age - Beck, Richard, 1967- (Broadleaf Books, 2021)
Five hundred years ago, the world was enchanted with angels and demons--God existed, and the devil was real. Today, we live in a post-Christian world characterized by doubt and skepticism. Richard Beck argues this is not evidence of a crisis of belief but a crisis of attention. Hunting Magic Eels reveals how we can cultivate an enchanted faith in a skeptical age and recover our ability to experience God as a living, vital presence.